1991
DOI: 10.1111/j.1471-6402.1991.tb00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Women Evaluated More Favorably Than Men?: An Analysis of Attitudes, Beliefs, and Emotions

Abstract: In an experiment in which male and female respondents evaluated the social category of women or men on several types of measures, analysis of respondents' attitudes toward the sexes and of the evaluative content of their beliefs established that they evaluated women more favorably than men. In addition, analysis of respondents' emotional reactions toward women and men did not yield evidence of negativity toward women at the emotional level. Nor did it appear that respondents' very positive evaluations of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
6
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(140 citation statements)
references
References 23 publications
13
111
6
8
Order By: Relevance
“…Hostile sexism refers to an openly antagonistic attitude toward women, whereas benevolent sexism refers to a subjectively positive orientation toward women that casts Òwomen as wonderful but fragile creatures who ought to be protected and provided for by menÓ (Glick et al, 2004, p. 715; see also Eagly, Mladinic, & Otto, 1991). Both types of sexism convey information about the division of structural power between the sexes by portraying women as weaker than men and more suitable for traditional domestic roles.…”
Section: Self-objectification and Sexist Ideologiesmentioning
confidence: 99%
“…Hostile sexism refers to an openly antagonistic attitude toward women, whereas benevolent sexism refers to a subjectively positive orientation toward women that casts Òwomen as wonderful but fragile creatures who ought to be protected and provided for by menÓ (Glick et al, 2004, p. 715; see also Eagly, Mladinic, & Otto, 1991). Both types of sexism convey information about the division of structural power between the sexes by portraying women as weaker than men and more suitable for traditional domestic roles.…”
Section: Self-objectification and Sexist Ideologiesmentioning
confidence: 99%
“…This domain appeared to be broadly suitable for this research question given society's mercurial attitudes towards women. Specifically, previous research has shown that there is a general tendency for women to be evaluated more positively than men (e.g., as the more helpful, kind and empathic gender: see Eagly, Mladinic, & Otto, 1991). However, research elsewhere has demonstrated that women are, simultaneously, all too often stereotyped as being ill-suited to leadership in occupational settings (see Eagly & Karau, 2002 for review).…”
mentioning
confidence: 99%
“…Although people generally associate more positive traits (e.g. happy, good) with women compared to men (known as the 'women are wonderful' effect; Eagly, Mladinic & Otto, 1991;Eagly & Mladinic, 1994), this is only true for status irrelevant characteristics. Women are subject to numerous negative stereotypes in relation to status relevant dimensions which draw the worth of their group into question (Cowan & Ullman, 2006) and justify their lower status position (e.g.…”
Section: Collective Self-esteem and Identity Threatmentioning
confidence: 99%
“…Although people generally associate more positive traits with women compared to men (known as the 'women are wonderful' effect; Eagly, Mladinic & Otto, 1991;Eagly & Mladinic, 1994), women are the targets of numerous negative stereotypes which draw the worth of their group into question and justify their lower status position (e.g. women are emotional; Jones, Farina, Hastorf, Markus, Miller, & Scott, 1984).…”
Section: Internalisation Of Sexismmentioning
confidence: 99%
See 1 more Smart Citation